Health risks status for two seaweeds of economic interest in Northwest Africa - Ndeye Coumba Bousso; Patrice Brehmer; Cheikhou Kane; Birgit Quack; Waly Ndianco Ndiaye; Hamet Diaw Diadhiou; Fulgence Diedhiou; Matthieu Waeles (Marine Pollution Bulletin, 2025)

Unusual holopelagic Sargassum mass beaching in Northwest Africa: Morphotypes, chemical composition, and potential valorisation - Ndeye Coumba Bousso; Patrice Brehmer; Waly Ndiaye; Valérie Stiger-Pouvreau; Cheikhou Kane; Maxime Gautier; Mamadou Faye; Anna Fricke; Hamet Diaw Diadhiou; Hanane Aroui Boukbida; Florian Weinberger; Balasubramaniyam Ramasamy; et al. (Science of The Total Environment, 2024)

From Monodisciplinary via Multidisciplinary to an Interdisciplinary Approach Investigating Air-Sea Interactions – a SOLAS Initiative - Christa Marandino; Erik van Doorn; Natasha McDonald; Martin Johnson; Bülent Açma; Emilie Brévière; Hanna Campen; Silvina Carou; Emilio Cocco; Sonja Endres; Nathalie Hilmi; Frances Hopkins; et al. (Coastal Management, 2020)

The influence of dissolved organic matter on the marine production of carbonyl sulfide (OCS) and carbon disulfide (CS 2 ) in the Peruvian upwelling - Sinikka T. Lennartz; Marc von Hobe; Dennis Booge; Henry C. Bittig; Tim Fischer; Rafael Gonçalves-Araujo; Kerstin B. Ksionzek; Boris P. Koch; Astrid Bracher; Rüdiger Röttgers; Birgit Quack; Christa A. Marandino (Ocean Science, 2019)
Oceanic emissions of the climate-relevant trace gases carbonyl sulfide (OCS) and carbon disulfide (CS2) are a major source to their atmospheric budget. Their current and future emission estimates are still uncertain due to incomplete process understanding and therefore inexact quantification across different biogeochemical regimes. Here we present the first concurrent measurements of both gases together with related fractions of the dissolved organic matter (DOM) pool, i.e., solid-phase extractable dissolved organic sulfur (DOSSPE, n=24, 0.16±0.04 µmol L−1), chromophoric (CDOM, n=76, 0.152±0.03), and fluorescent dissolved organic matter (FDOM, n=35), from the Peruvian upwelling region (Guayaquil, Ecuador to Antofagasta, Chile, October 2015). OCS was measured continuously with an equilibrator connected to an off-axis integrated cavity output spectrometer at the surface (29.8±19.8 pmol L−1) and at four profiles ranging down to 136 m. CS2 was measured at the surface (n=143, 17.8±9.0 pmol L−1) and below, ranging down to 1000 m (24 profiles). These observations were used to estimate in situ production rates and identify their drivers. We find different limiting factors of marine photoproduction: while OCS production is limited by the humic-like DOM fraction that can act as a photosensitizer, high CS2 production coincides with high DOSSPE concentration. Quantifying OCS photoproduction using a specific humic-like FDOM component as proxy, together with an updated parameterization for dark production, improves agreement with observations in a 1-D biogeochemical model. Our results will help to better predict oceanic concentrations and emissions of both gases on regional and, potentially, global scales.

Simulating the spread of disinfection by-products and anthropogenic bromoform emissions from ballast water discharge in Southeast Asia - Josefine Maas; Susann Tegtmeier; Birgit Quack; Arne Biastoch; Jonathan V. Durgadoo; Siren Rühs; Stephan Gollasch; Matej David (Ocean Science, 2019)
Ballast water treatment is required for vessels to prevent the introduction of potentially invasive neobiota. Some treatment methods use chemical disinfectants which produce a variety of halogenated compounds as disinfection by-products (DBPs). One of the most abundant DBPs from oxidative ballast water treatment is bromoform (CHBr3), for which we find an average concentration of 894±560 nmol L−1 (226±142 µg L−1) in the undiluted ballast water from measurements and the literature. Bromoform is a relevant gas for atmospheric chemistry and ozone depletion, especially in the tropics where entrainment into the stratosphere is possible. The spread of DBPs in the tropics over months to years is assessed here for the first time. With Lagrangian trajectories based on the NEMO-ORCA12 model velocity field, we simulate DBP spread in the sea surface and quantify the oceanic bromoform concentration and emissions to the atmosphere from ballast water discharge at major harbours in the tropical region of Southeast Asia. The exemplary simulations of two important regions, Singapore and the Pearl River Delta, reveal major transport pathways of DBPs and anthropogenic bromoform concentrations in the sea surface. Based on our simulations, we expect DBPs to spread into the open ocean, along the coast and through advection with monsoon-driven currents into the North Pacific and Indian Ocean. Furthermore, anthropogenic bromoform concentrations and emissions are predicted to increase locally around large harbours. In the sea surface around Singapore, we estimate an increase in bromoform concentration by 9 % compared to recent measurements. In a moderate scenario in which 70 % of the ballast water is chemically treated, bromoform emissions to the atmosphere can locally exceed 1000 pmol m−2 h−1 and double climatological emissions. In the Pearl River Delta all bromoform is directly outgassed, which leads to an additional bromine (Br) input into the atmosphere of 495 kmol Br a−1 (∼42 t CHBr3). For Singapore ports the additional atmospheric Br input is calculated as 312 kmol Br a−1 (∼ 26 t CHBr3). We estimate a global anthropogenic Br input from ballast water into the atmosphere of up to 13 Mmol a−1. This is 0.1 % of global Br input from background bromoform emissions and thus not relevant for stratospheric ozone depletion.

A New Perspective at the Ship-Air-Sea-Interface: The Environmental Impacts of Exhaust Gas Scrubber Discharge - Sonja Endres; Frank Maes; Frances Hopkins; Katherine Houghton; Eva M. Mårtensson; Johannes Oeffner; Birgit Quack; Pradeep Singh; David Turner (Frontiers in Marine Science, 2018)

Future emissions of marine halogenated very-short lived substances under climate change - Franziska Ziska; Birgit Quack; Susann Tegtmeier; Irene Stemmler; Kirstin Krüger (Journal of Atmospheric Chemistry, 2017)